2016
DOI: 10.1213/ane.0000000000001299
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Best Fit: A Comparison of Response Surface Models for Midazolam and Alfentanil Sedation in Procedures With Varying Stimulation

Abstract: The reduced Greco model had the lowest objective function value and AICc and thus the best fit. This model was reliable with acceptable predictive ability based on adequate clinical correlation. We suggest that this model has practical clinical value for patients undergoing procedures with varying degrees of stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…We had to convert alfentanil to remifentanil according to their potency before calculation for RSM’s accuracy. Our previous studies indicated that such conversion did not affect these RSMs’ applications to sedate patients undergoing medical procedures 1012 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We had to convert alfentanil to remifentanil according to their potency before calculation for RSM’s accuracy. Our previous studies indicated that such conversion did not affect these RSMs’ applications to sedate patients undergoing medical procedures 1012 .…”
Section: Discussionmentioning
confidence: 97%
“…Response surface models (RSMs), unlike traditional isobolograms that represent the concentrations of combirned agents to produce a single degree of drug effect ( e.g ., a C50 level—the concentration producing 50% of maximal drug effect), characterise the complete spectrum of interaction between two or more agents for possible levels of concentration and effects in response to a given stimulus 9 . Several medical procedures requiring moderate sedation and analgesia have evaluated these published RSMs 1012 . Using a modified Greco construct equation 13 , LaPierre et al .…”
Section: Introductionmentioning
confidence: 99%
“…For each pharmacodynamic response, data were combined to build a three-dimensional response surface using a naïve-pooled technique. Model parameters were determined with an iterative approach minimising the À2 times the logarithm of maximal likelihood (À2LL), 15 as follows…”
Section: Discussionmentioning
confidence: 99%
“…Assuming a χ2 distribution with 1 degree of freedom and P = .05, if the difference between the objective function values (OFV) > 3.84, it would be considered significantly different. 15 The correlation coefficient of the regression parameter estimates was used to evaluate how well the final model described the observed data. A value of the correlation coefficient ≥.7 indicates that the observed response could be well predicted by the model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation